Client views of counselor directives （指导）: A qualitative study in china. Issue 2 (3rd April 2022) - Duan, Changming; Hill, Clara; Jiang, Guangrong; Li, Shengnan; Duan, Xinghua; Li, Fenglan; Hu, Bo; Yu, Lixia; Du, Min
ABSTRACT: In order to understand client views of counselor' use of directives, we conducted in-depth interviews with nine clients immediately after they completed a session at a university counseling center in China. The results, derived by using Consensus Qualitative Research (CQR), revealed that participants generally expected counselors to give directives, reported having received them, and felt good after receiving them. In addition, clients perceived some non-directive counselor interventions as being directives. Clients felt discontented when they did not receive as many directives as they wanted and when they received directives that did not fit their needs. Clients indicated that they would implement only those directives that they anticipated would have a clear benefit and would not implement those that seemed difficult to do. The results shed light on outcomes related to directives, conditions needed for directives to be implemented, mechanisms by which directives lead to positive change, and client feelings after receiving counselor directives, all within the context of the Chinese culture. One implication of the results is that training programs need to focus on training how to use directives when working with Chinese clients.